2009
DOI: 10.1002/cne.21986
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord compression injury in adult rats initiates changes in dorsal horn remodeling that may correlate with development of neuropathic pain

Abstract: Spinal cord injury commonly causes chronic, neuropathic pain. The mechanisms are poorly understood but may include structural plasticity within spinal and supraspinal circuits. Our aim was to determine whether structural remodeling within the dorsal horn rostral to an incomplete injury differs from a complete spinal cord transection. Four immunohistochemical populations of primary afferent C-fibers, and descending catecholamine and serotonergic projections, were examined in segments T9-T12 at 2 and 12 weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 71 publications
7
27
1
Order By: Relevance
“…Each of the primary antibodies has been characterized extensively in previous studies (Forrest and Keast, 2008; Kalous et al, 2009; Kiasalari et al, 2010) and showed general patterns of staining comparable to these earlier reports. To identify neurons that could potentially be influenced by GFLs, we used antibodies raised against the preferred receptors for GDNF (GFRα1), neurturin (GFRα2), and artemin (GFRα3).…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Each of the primary antibodies has been characterized extensively in previous studies (Forrest and Keast, 2008; Kalous et al, 2009; Kiasalari et al, 2010) and showed general patterns of staining comparable to these earlier reports. To identify neurons that could potentially be influenced by GFLs, we used antibodies raised against the preferred receptors for GDNF (GFRα1), neurturin (GFRα2), and artemin (GFRα3).…”
Section: Methodssupporting
confidence: 62%
“…TRPV1 is a marker of polymodal nociceptor neurons that is expressed by the majority of bladder afferent neurons (Bennett et al, 2003). Previous studies of DRGs at other spinal levels have shown that the majority of CGRP-IR neurons express TRPV1 (Kiasalari et al, 2010) and that GFRα3-IR is expressed in a sub-population of CGRP-IR neurons (Orozco et al, 2001; Kalous et al, 2009). From these previous studies we also predicted that GFRα1- and GFRα2-IR would be found in the non-peptidergic population (Bennett et al, 1998; Kalous et al, 2007, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in some of these reports the density of CGRPpositive fibers decreased in some dorsal horn laminae while increasing in others. Furthermore, other studies have described only decreases of CGRP-positive fiber density across most of the dorsal horn after complete spinal transection (Kalous et al, 2007) and spinal compression injury (Kalous et al, 2009). Differences also appear to exist between the growth-promoting effects of central and peripheral injury; a conditioning lesion of the sciatic nerve enhances the intrinsic growth state of some DRG neurons but, in contrast to our findings after SCI, not those expressing CGRP (Kalous and Keast, 2010).…”
Section: Bedi Et Alcontrasting
confidence: 56%
“…To increase assay sensitivity, we separately assessed neurite outgrowth in peptidergic C-fiber neurons that are CGRP-immunoreactive (Orozco et al, 2001; Forrest and Keast, 2008; Kalous et al, 2009; Keast et al, 2010; Forrest et al, 2013). These CGRP-positive C-fibers in DRGs express the ARTN receptor, GFRα3, while the CGRP-negative neurons express receptors of other GFLs (Bennett et al, 1998; Senba et al, 2007).…”
Section: Resultsmentioning
confidence: 99%